Graphene microcrystalline glass for chip packaging and preparation method thereof

By blending glass powder of specific components with graphene and heat treatment at low temperature, the problem of acid resistance of microcrystalline glass in the prior art is solved, and high-performance graphene microcrystalline glass has good dielectric properties, thermal conductivity and Bending strength, suitable for chip packaging.

CN119285241APending Publication Date: 2025-01-10SHANDONG YUHANG PAIMENG NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411386771.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the prior art, microcrystalline glass used in chip packaging requires additional alkali metal and MgO during low temperature sintering, resulting in a decrease in acid resistance and making it difficult to achieve a material with good dielectric properties, thermal conductivity and bending strength.

Method used

Graphene microcrystalline glass is prepared by low-temperature heat treatment by blending glass powder with specific ingredients with graphene and nucleating agent in a specific proportion, including SiO2, Al2O3, MgO, H3BO3, CaCO3, NaCO3, LiCO3, ZrO2, TiO2, Y2O3, etc. The composition is that the amount of graphene is 0.1-0.5%, and heat treatment is carried out under a gas protection atmosphere not less than 600°C.

Benefits of technology

It significantly improves the thermal conductivity, bending strength and acid resistance of microcrystalline glass, achieves low-temperature nucleation, reduces production conditions, and ensures the performance stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005071128380000091
    Figure BDA0005071128380000091
  • Figure BDA0005071128380000101
    Figure BDA0005071128380000101
Patent Text Reader

Abstract

The invention provides graphene microcrystalline glass for chip packaging and a preparation method thereof, and relates to the field of electronic packaging, the graphene microcrystalline glass comprises glass powder and a graphene component, the glass powder comprises the following components by weight: 40-52 parts of SiO2, 18-20 parts of Al2O3, 20-24 parts of MgO, 6 parts of H3BO3, 5-6 parts of CaCO3, 2-6 parts of NaCO3, 3 parts of LiCO3, 3-5 parts of ZrO2, 6-8 parts of TiO2, and 1-2 parts of Y2O3; the graphene component adopts graphene or graphene oxide, and the use amount of the graphene component is 0.1-0.5% of the weight of the glass powder; the glass ceramic prepared by blending and sintering the glass powder raw material with specific components, the graphene and the specific nucleating agent according to a specific proportion has the advantages that the heat-conducting property, the bending strength and the acid resistance are obviously improved, glass ceramic particles can be generated at the lowest temperature of 600 DEG C, the nucleating temperature is low, and the production conditions are greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electronic packaging of integrated circuits, chips and semiconductors, and in particular to a graphene microcrystalline glass for chip packaging and a preparation method thereof. Background Art

[0002] With the rapid development of many high-tech technologies, such as information technology and microelectronics, the rapid development of AI technology and the development of computing power technology represented by Chatgpt have put forward higher requirements for the computing power of chips. High-computing chips require higher power, and high power will generate more heat. The development of technology has put forward higher requirements for corresponding materials. Specifically in the field of electronic packaging, packaging materials are mainly used for substrate materials, circuit wiring, component frames, interlayer filling media and sealing. How to improve the heat dissipation and dielectric properties of packaging materials is an industry technical problem that needs to be solved urgently. The preparation of materials with excellent performance and meeting packaging requirements has become the first difficulty to break through in the industry. At present, packaging materials are required to have good sealing performance, low cost, low sintering temperature, good dielectric properties, thermal expansion coefficient matching silicon, and co-firing with conductive metals such as gold, silver and copper.

[0003] Glass-ceramics is a basic glass with a specific composition that is crystallized and heat treated under a certain temperature system, so that a large number of tiny crystals are uniformly precipitated in the glass, thus forming a dense multiphase complex of microcrystalline phase and glass phase. Glass-ceramics has many advantages: the mechanical strength of glass-ceramics is much higher than that of ordinary glass, and even exceeds that of some ceramic materials; it is more ductile than glass and not easy to break; it has higher hardness and good wear resistance; it has good chemical stability and has good resistance to hydration, hydration and cation exchange; it has low dielectric loss rate and is suitable for high-frequency insulation and high-voltage insulation casing materials; it has a low thermal expansion coefficient, good thermal vibration stability, and a high temperature point for high-temperature softening.

[0004] Glass-ceramics is a solid composite material with a crystal phase and a glass phase. As a composite material, glass-ceramics is composed of at least three components: SiO2, Al2O3, and MgO. SiO2, as a glass network former, is an important component of glass formation.

[0005] As the most common silicate network former, SiO2 has excellent performance mainly due to its special three-dimensional structure. SiO2 is a three-dimensional structure of silicon-oxygen tetrahedrons connected at the same top. Although the Si-O bond is a polar covalent bond, the positive and negative charge centers of the entire silicon-oxygen tetrahedron coincide. However, the melting temperature of quartz glass is high, and additives (alkali metals) need to be added to lower the melting temperature of quartz glass. Excessive alkali metals will destroy the silicon-oxygen network, destroy the structure, and thus affect its performance.

[0006] As an intermediate oxide of the basic component of glass-ceramics, the presence of Al2O3 will improve the mechanical and physical properties of the material, but will weaken the electrical properties of glass-ceramics. In silicate glass, Al2O3 can increase the dielectric loss and dielectric constant of the material. In some glasses with high requirements for electrical properties, Al2O3 is contained in small amounts or not at all.

[0007] MgO has two main coordination states (4 or 6) in the glass network, but in most silicate structures, it mainly exists in the form of octahedron, which is an exosome of the network. MgO can reduce the high-temperature viscosity of glass, allowing the material to be liquid-phase sintered at a relatively low temperature, but excessive addition of MgO will greatly reduce the acid resistance of the glass. Microcrystalline glass requires a process for crystal growth. When the glass is annealed in a furnace, the alkali metal oxides inside the material will move to the surface, thereby affecting the acid resistance of the microcrystalline glass.

[0008] In the prior art, the patent document with publication number CN116730619A discloses a low-loss microcrystalline glass material for LTCC and a preparation method thereof, wherein the dielectric constant is 4 to 6.5, the sintering temperature is 780 to 830°C, and pre-firing at 400 to 500°C is required before sintering.

[0009] In the field of electronic packaging of integrated circuits, chips, and semiconductors, a microcrystalline glass that can be sintered at low temperatures is needed, and because the process often involves pickling treatment, the microcrystalline glass is required to have good acid and alkali resistance. However, in order to achieve low-temperature sintering, the existing technology requires the addition of more alkali metals and more MgO, but the addition of these two materials will affect the acid resistance of the packaging glass. Therefore, there is a need for a material that can block the precipitation of alkali metals, and the addition can promote the formation of microcrystalline glass crystals, promote the improvement of dielectric properties, and stabilize the performance of the product.

[0010] In the prior art, the patent document with publication number CN117466535A discloses a microcrystalline glass with excellent acid and alkali resistance, which obtains a microcrystalline glass with excellent acid and alkali resistance by strictly controlling the range of oxide components in the microcrystalline glass of lithium aluminum silicon system. Specifically, the obtained microcrystalline glass loses weight per unit area of ​​0.024g / CM after being immersed in 5% HCl at 95°C for 24h. 2 , after immersion in 10% HF at 20°C for 20 minutes, the weight loss per unit area reached 6.924g / CM 2 .

[0011] Based on this, the present application aims to propose a graphene microcrystalline glass for chip packaging that has good dielectric properties as well as good acid resistance, thermal conductivity, and bending strength, and also proposes a preparation method with low nucleation temperature. Summary of the invention

[0012] In view of the above problems existing in the prior art, the present invention provides a graphene glass-ceramic for chip packaging and a preparation method thereof.

[0013] The technical solution of the present invention to solve the above technical problems is as follows:

[0014] On the one hand, the present invention provides a graphene glass-ceramic for chip packaging, characterized in that its composition includes glass powder and graphene components, wherein:

[0015] The glass powder is composed of the following components by weight: 40-52 parts of SiO2, 18-20 parts of Al2O3, 0-24 parts of MgO2, 6 parts of H3BO3, 5-6 parts of CaCO3, 2-6 parts of NaCO3, 3 parts of LiCO3, 3-5 parts of ZrO2, 6-8 parts of TiO2, and 1-2 parts of Y2O3;

[0016] The graphene component is graphene or graphene oxide, and its usage is 0.1-0.5% of the weight of the glass powder.

[0017] In this scheme, MgO, Al2O3, SiO2, H3BO3, CaCO3, NaCO3, and LiCO3 are the substrates of microcrystalline glass, ZrO2, TiO2, and Y2O3 are composite nucleating agents, and 1-10 layers of graphene are additives.

[0018] As a preferred embodiment, the graphene glass-ceramics is composed of the following components by weight: 52 parts of SiO2, 20 parts of Al2O3, 20 parts of MgO, 6 parts of H3BO3, 5 parts of CaCO3, 2 parts of NaCO3, 3 parts of LiCO3, 5 parts of ZrO2, 6 parts of TiO2, and 2 parts of Y2O3; the amount of graphene component is 0.2% of the weight of the glass powder.

[0019] Furthermore, the flake diameter of the graphene or graphene oxide is 500nm-40μm.

[0020] On the other hand, the present invention provides a method for preparing the above-mentioned graphene glass-ceramics for chip packaging, characterized in that it comprises the following steps:

[0021] S1: Weigh the formula amount of SiO2, Al2O3, MgO, H3BO3, CaCO3, NaCO3, LiCO3, ZrO2, TiO2, Y2O3, and ball mill;

[0022] S2: Melting the material in step S1 and then keeping it warm to obtain a glass melt;

[0023] S3: quenching the molten glass with water, taking out the glass slag, drying, crushing, grinding and sieving to obtain fine glass powder;

[0024] S4: Weigh the graphene or graphene oxide powder in the formula amount, and ball-mill it with the glass fine powder in S3 to obtain a mixed powder;

[0025] S5: Casting the mixed powder into a film or pressing the dry powder into a sheet; in addition, punching, filling, screen printing and other process operations can be performed according to the circuit design requirements;

[0026] S6: Heat treatment is performed under a gas protective atmosphere at a temperature not lower than 600°C to produce graphene glass-ceramics. The gas protective atmosphere is mainly used to isolate the influence of oxygen on the product.

[0027] Furthermore, the melting temperature in step S2 is 1450-1650°C, and the holding temperature is preferably 1350-1500°C.

[0028] Furthermore, the powder is ground in step S3 and then passed through a 325-mesh sieve.

[0029] Furthermore, the gas protection atmosphere in step S6 adopts an inert gas, preferably nitrogen or a nitrogen-hydrogen mixed gas with a volume fraction of 5% hydrogen:95% nitrogen.

[0030] The beneficial effects of the present invention are:

[0031] 1. The present invention mixes glass powder raw materials with specific components with graphene and specific nucleating agents in a specific ratio, and the thermal conductivity, bending strength and acid resistance of the microcrystalline glass obtained by sintering are significantly improved;

[0032] 2. Under the specific formula and process of the present invention, microcrystalline glass particles can be generated at a minimum temperature of 600°C, and the nucleation temperature is low, which greatly reduces the production conditions. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0034] Example 1

[0035] The preparation of the graphene glass-ceramics for chip packaging in this embodiment is as follows:

[0036] S1. Raw material preparation: Weigh the following composition by weight: 52 parts of SiO2, 20 parts of Al2O3, 20 parts of MgO, 6 parts of H3BO3, 5 parts of CaCO3, 2 parts of NaCO3, 3 parts of LiCO3, 5 parts of ZrO2, 6 parts of TiO2, and 2 parts of Y2O3. Weigh the above materials and ball mill for 2 hours;

[0037] S2. Melting and clarification of glass: melt the weighed material at 1550°C for 3h, then cool to 1400°C and keep warm for 2h to obtain a glass melt with uniform composition;

[0038] S3. Water quenching of glass: The glass solution was added to deionized water for water quenching, the glass slag was removed, dried, crushed, and ground through a 325 mesh sieve to obtain a glass fine powder;

[0039] S4. Weigh 0.1% by weight of redox graphene in glass-ceramic powder, and ball-mill with the glass-ceramic powder for 2 h to obtain a mixed powder;

[0040] S5. Weigh the mixed powder and press the dry powder into tablets;

[0041] S6. Heat treatment is performed at 600°C in a nitrogen-hydrogen mixed gas atmosphere of 5% hydrogen:95% nitrogen to promote the formation of crystals in the glass system, and the preparation of graphene microcrystalline glass is completed.

[0042] Example 2

[0043] The preparation of the graphene glass-ceramics for chip packaging in this embodiment is as follows:

[0044] S1. Raw material preparation: Weigh the following composition by weight: 40 parts of SiO2, 18 parts of Al2O3, 24 parts of MgO, 6 parts of H3BO3, 6 parts of CaCO3, 6 parts of NaCO3, 3 parts of LiCO3, 3 parts of ZrO2, 8 parts of TiO2, and 1 part of Y2O3. Weigh the above materials and ball mill for 2 hours;

[0045] S2. Melting and clarification of glass: melt the weighed material at 1500°C for 2h, then cool to 1350°C and keep warm for 2h to obtain a glass melt with uniform composition;

[0046] S3. Water quenching of glass: The glass solution was added to deionized water for water quenching, the glass slag was removed, dried, crushed, and ground through a 325 mesh sieve to obtain a glass fine powder;

[0047] S4. Weigh 0.3% by weight of mechanically exfoliated graphene of glass-ceramic powder, with a graphene sheet diameter range of about 10-20 μm, prepare a saturated or nearly saturated graphene dispersion, and then evenly disperse the glass powder therein to obtain a mixture, filter and dry to obtain a mixed powder;

[0048] S5. Weigh the mixed powder and press the dry powder into tablets;

[0049] S6. Perform heat treatment at 600°C in an atmosphere of a nitrogen-hydrogen mixed gas of 5% hydrogen and 95% nitrogen to promote the formation of crystals in the glass system, and the preparation of graphene microcrystalline glass is completed.

[0050] Example 3

[0051] The preparation of the graphene glass-ceramics for chip packaging in this embodiment is as follows:

[0052] S1. Raw material preparation: Weigh the following composition by weight: 52 parts of SiO2, 18 parts of Al2O3, 24 parts of MgO, 6 parts of H3BO3, 6 parts of CaCO3, 6 parts of NaCO3, 3 parts of LiCO3, 3 parts of ZrO2, 8 parts of TiO2, and 1 part of Y2O3. Weigh the above materials and ball mill for 2 hours;

[0053] S2. Melting and clarification of glass: melt the weighed material at 1500°C for 2h, then cool to 1350°C and keep warm for 2h to obtain a glass melt with uniform composition;

[0054] S3. Water quenching of glass: The glass solution was added to deionized water for water quenching, the glass slag was removed, dried, crushed, and ground through a 325 mesh sieve to obtain a glass fine powder;

[0055] S4. Weigh 0.5% by weight of mechanically exfoliated graphene with a glass-ceramic powder, wherein the diameter of the graphene flakes is about 10-20 μm; ball mill for 2 h to obtain a mixed powder;

[0056] S5. Weigh the mixed powder and press the dry powder into tablets;

[0057] S6. Perform heat treatment at 600°C in an atmosphere of a nitrogen-hydrogen mixed gas of 5% hydrogen and 95% nitrogen to promote the formation of crystals in the glass system, and the preparation of graphene microcrystalline glass is completed.

[0058] Comparative Example 1

[0059] The preparation of the glass-ceramics in this comparative example is basically the same as that in Example 1, except that step S4 in Example 1 is not included, that is, the raw material does not include graphene, and the details are as follows:

[0060] S1. Raw material preparation: Weigh the following composition by weight: 52 parts of SiO2, 20 parts of Al2O3, 20 parts of MgO, 6 parts of H3BO3, 5 parts of CaCO3, 2 parts of NaCO3, 3 parts of LiCO3, 5 parts of ZrO2, 6 parts of TiO2, and 2 parts of Y2O3; weigh the above materials and ball mill for 2 hours;

[0061] S2. Melting and clarification of glass: melt the weighed material at 1550°C for 3h, then cool to 1400°C and keep warm for 2h to obtain a glass melt with uniform composition;

[0062] S3. Water quenching of glass: The glass solution was added to deionized water for water quenching, the glass slag was removed, dried, crushed, and ground through a 325 mesh sieve to obtain a glass fine powder;

[0063] S4. Weigh glass fine powder and press dry powder into tablets;

[0064] S5. Heat treatment is performed at 850°C in a nitrogen-hydrogen mixed gas atmosphere of 5% hydrogen:95% nitrogen to promote the formation of crystals in the glass system to produce microcrystalline glass.

[0065] Comparative Example 2

[0066] The preparation of the microcrystalline glass in this comparative example is basically the same as that in Example 1, except that the nucleating agent (5 parts of ZrO2, 6 parts of TiO2, 2 parts of Y2O3) is replaced by ZrO2 and TiO2 in a mass ratio of 1:1, and the total amount of the nucleating agent remains unchanged.

[0067] The preparation of the graphene glass-ceramics for chip packaging in this embodiment is as follows:

[0068] S1. Raw material preparation: Weigh the following composition by weight: 52 parts of SiO2, 20 parts of Al2O3, 20 parts of MgO, 6 parts of H3BO3, 5 parts of CaCO3, 2 parts of NaCO3, 3 parts of LiCO3, 6.5 parts of ZrO2, 6.5 parts of TiO2, and 0 parts of Y2O3. Weigh the above materials and ball mill for 2 hours;

[0069] S2. Melting and clarification of glass: melt the weighed material at 1550°C for 3h, then cool to 1400°C and keep warm for 2h to obtain a glass melt with uniform composition;

[0070] S3. Water quenching of glass: The glass solution was added to deionized water for water quenching, the glass slag was removed, dried, crushed, and ground through a 325 mesh sieve to obtain a glass fine powder;

[0071] S4. Weigh 0.1% by weight of graphene in glass-ceramic powder and ball-mill it with the glass-ceramic powder for 2 hours to obtain a mixed powder;

[0072] S5. Weigh the mixed powder and press the dry powder into tablets;

[0073] S6. Perform heat treatment at 850°C in a nitrogen-hydrogen mixed gas atmosphere of 5% hydrogen and 95% nitrogen to promote the formation of crystals in the glass system and produce graphene microcrystalline glass.

[0074] Comparative Example 3

[0075] The preparation of the glass-ceramics in this comparative example is basically the same as that in comparative example 4, except that the heat treatment temperature in step S6 is 600° C. The result shows that the formability is poor.

[0076] Comparative Example 4

[0077] The preparation of the microcrystalline glass in this comparative example is basically the same as that in Example 1, except that the nucleating agent (5 parts of ZrO2, 6 parts of TiO2, and 2 parts of Y2O3) is replaced by ZrO2 and Y2O3 in a mass ratio of 1:1, and the total amount of the nucleating agent remains unchanged.

[0078] The preparation of the graphene glass-ceramics for chip packaging in this embodiment is as follows:

[0079] S1. Raw material preparation: A graphene glass-ceramic for electronic packaging, weigh the following composition by weight: 52 parts of SiO2, 20 parts of Al2O3, 20 parts of MgO, 6 parts of H3BO3, 5 parts of CaCO3, 2 parts of NaCO3, 3 parts of LiCO3, 6.5 parts of ZrO2, 0 parts of TiO2, and 6.5 parts of Y2O3. Weigh the above materials and ball mill for 2 hours;

[0080] S2. Melting and clarification of glass: melt the weighed material at 1550°C for 3h, then cool to 1400°C and keep warm for 2h to obtain a glass melt with uniform composition;

[0081] S3. Water quenching of glass: The glass solution was added to deionized water for water quenching, the glass slag was removed, dried, crushed, and ground through a 325 mesh sieve to obtain a glass fine powder;

[0082] S4. Weigh 0.1% by weight of redox graphene in glass-ceramic powder, and ball-mill with the glass-ceramic powder for 2 h to obtain a mixed powder;

[0083] S5. Weigh the mixed powder and press the dry powder into tablets;

[0084] S6. Perform heat treatment at 850°C in a nitrogen-hydrogen mixed gas atmosphere of 5% hydrogen and 95% nitrogen to promote the formation of crystals in the glass system and produce graphene microcrystalline glass.

[0085] Comparative Example 5

[0086] The preparation of the glass-ceramics in this comparative example is basically the same as that in comparative example 5, except that the heat treatment temperature in step S6 is 600° C. The result shows that the formability is poor.

[0087] Comparative Example 6

[0088] The preparation of the microcrystalline glass in this comparative example is basically the same as that in Example 1, except that the amount of graphene therein is replaced by 4%.

[0089] The preparation of the graphene glass-ceramics for chip packaging in this embodiment is as follows:

[0090] S1. Raw material preparation: Weigh the following composition by weight: 52 parts of SiO2, 20 parts of Al2O3, 20 parts of MgO, 6 parts of H3BO3, 5 parts of CaCO3, 2 parts of NaCO3, 3 parts of LiCO3, 5 parts of ZrO2, 6 parts of TiO2, and 2 parts of Y2O3. Weigh the above materials and ball mill for 2 hours;

[0091] S2. Melting and clarification of glass: melt the weighed material at 1550°C for 3h, then cool to 1400°C and keep warm for 2h to obtain a glass melt with uniform composition;

[0092] S3. Water quenching of glass: The glass solution was added to deionized water for water quenching, the glass slag was removed, dried, crushed, and ground through a 325 mesh sieve to obtain a glass fine powder;

[0093] S4. Weigh 4% by weight of graphene in glass-ceramic powder and ball-mill it with the glass-ceramic powder for 2 hours to obtain a mixed powder;

[0094] S5. Weigh the mixed powder and press it into dry powder tablets; practice shows that the dry powder cannot be pressed into a dense tablet, but can be formed into a tablet after adding a small amount of water to moisten it;

[0095] S6. Perform heat treatment at 600°C in a nitrogen-hydrogen mixed gas atmosphere of 5% hydrogen and 95% nitrogen to promote the formation of crystals in the glass system and prepare graphene microcrystalline glass. The prepared microcrystalline glass has obvious pores on its surface.

[0096] The above embodiments and comparative examples were tested for thermal expansion coefficient, thermal conductivity, dielectric constant, bending strength, acid loss and other performances, and the test results are shown in Table 1. Among them, the thermal expansion coefficient, thermal conductivity, dielectric constant and bending strength were tested by thermal expansion coefficient tester, thermal conductivity tester, dielectric constant tester and bending strength universal testing machine, respectively. The method for determining the acid loss is: using an analytical balance to weigh the mass of the glass sample before and after the acid resistance test as m0 and m1 respectively, the area of ​​the glass sample is s, and the weight loss per unit area x = (m0-m1) / s. Specifically, the crystallized glass sheet was immersed in the following two acid conditions to test its acid and alkali resistance: 1) standing at 95°C for 24h in a hydrochloric acid solution with a mass concentration of 5% (abbreviated as "HCl-5%-95°C-24h"); 2) standing at 20°C for 20min in a hydrofluoric acid solution with a mass concentration of 10% (abbreviated as "HF-10%-20°C-20min");

[0097] Table 1

[0098]

[0099]

Claims

1. A graphene glass-ceramic for chip packaging, characterized in that: Its components include glass powder and graphene components, wherein: The glass powder is composed of the following components by weight: 40-52 parts of SiO2, 18-20 parts of Al2O3, 0-24 parts of MgO2, 6 parts of H3BO3, 5-6 parts of CaCO3, 2-6 parts of NaCO3, 3 parts of LiCO3, 3-5 parts of ZrO2, 6-8 parts of TiO2, and 1-2 parts of Y2O3; The graphene component is graphene or graphene oxide, and its usage is 0.1-0.5% of the weight of the glass powder.

2. The graphene glass-ceramics for chip packaging according to claim 1, characterized in that: The glass powder is composed of the following components by weight: 52 parts of SiO2, 20 parts of Al2O3, 20 parts of MgO, 6 parts of H3BO3, 5 parts of CaCO3, 2 parts of NaCO3, 3 parts of LiCO3, 5 parts of ZrO2, 6 parts of TiO2, and 2 parts of Y2O3; the amount of graphene component used is 0.2% of the weight of the glass powder.

3. The graphene glass-ceramics for chip packaging according to claim 1, characterized in that: The sheet diameter of the graphene or graphene oxide is 500nm-40μm.

4. The method for preparing graphene glass-ceramics for chip packaging according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Weigh the formula amount of SiO2, Al2O3, MgO, H3BO3, CaCO3, NaCO3, LiCO3, ZrO2, TiO2, Y2O3, and ball mill; S2: Melting the material in step S1 and keeping it warm to obtain a glass melt; S3: quenching the molten glass with water, taking out the glass slag, drying, crushing, grinding and sieving to obtain fine glass powder; S4: Weighing a formulated amount of graphene or graphene oxide and blending it with the glass fine powder of step S3 to obtain a mixed powder; S5: Casting the mixed powder into sheets or pressing dry powder into tablets; S6: heat treatment under a gas protective atmosphere at a temperature not lower than 600° C. to produce graphene glass-ceramics.

5. The preparation method according to claim 4, characterized in that: The preparation method of the mixed powder in step S4 is: weigh the formulated amount of graphene or graphene oxide powder, and ball-mill it with the glass fine powder in S3 to obtain the mixed powder.

6. The preparation method according to claim 4, characterized in that: The preparation method of the mixed powder in step S4 is: weigh a formulated amount of graphene or graphene oxide dispersion liquid, evenly disperse it with the glass fine powder in step S3 to obtain a mixture, filter it and then dry it to obtain a mixed powder.

7. The preparation method according to claim 4, characterized in that: The melting temperature in step S2 is between 1450°C and 1650°C.

8. The preparation method according to claim 4, characterized in that: The powder in step S3 is ground and passed through a 325-mesh sieve.

9. The preparation method according to claim 4, characterized in that: The gas protection atmosphere in step S6 is an inert gas.

10. The preparation method according to claim 9, characterized in that: The gas protection atmosphere in step S6 is nitrogen or a nitrogen-hydrogen mixed gas with a volume fraction of 5% hydrogen:95% nitrogen.

Citation Information

Patent Citations

  • Low-loss microcrystalline glass material for LTCC (low temperature co-fired ceramic) and preparation method of low-loss microcrystalline glass material

    CN116730619A

  • Glass ceramic with excellent acid and alkali resistance as well as preparation method and application of glass ceramic

    CN117466535A